Women In Changing Society - Jones, Rhyland (Ed_Tech Press, 2018)
This book has special concerns on, various aspects of feminism and queries of paradigm shift in women studies. A book to further reading in the light of the documents consulted and used in the chapters which may be a foundation for any serious researcher on women in the development process.